Managing Severe Post-Stroke Catatonia in a Medically Complex Patient: Electroconvulsive Therapy During Thromboembolic Disease and Intracerebral Hemorrhage - Yu, Daniel-Jiajun; Masson, Violaine; Riverin-Deschênes, Bruno (Santé mentale au Québec, 2026)
Catatonia is a neuropsychiatric syndrome with diverse etiologies and substantial morbidity in older adults, particularly when thromboembolic complications occur. While affective disorders are frequent precipitants, catatonia following cerebrovascular events remains under‑recognized.A 71‑year‑old woman with recent multifocal ischemic stroke, vascular neurocognitive disorder and prior depression presented with a subacute syndrome of immobility and mutism. At initial outpatient evaluation, she exhibited marked catatonic signs (Bush-Francis Catatonia Rating Scale [BFCRS] 31/69). Lorazepam produced only partial improvement and was limited by sedation and dysarthria.Given pharmacological resistance and tolerability issues, electroconvulsive therapy (ECT) was initiated, with clinical improvement after 2 sessions. ECT was interrupted due to COVID-19 infection, accompanied by proximal deep vein thrombosis and pulmonary embolism managed with apixaban. Within 1 month of ECT interruption, catatonia symptoms reemerged. After multidisciplinary consultations, ECT was cautiously restarted. Eleven consecutive ECT sessions were then performed, with varying frequency due to confusional states emerging at 3 sessions per week. A subsequent mechanical fall, along with neuroimaging findings consistent with a subacute intracerebral hemorrhage, prompted early discontinuation of ECT. Catatonia relapsed 2 months after discontinuation. Repetitive transcranial magnetic stimulation (rTMS) was tried without effect, and ECT was restarted with success and maintained. Adjunctive memantine and mirtazapine were trialed without clear benefit, while suspected underlying post-stroke depression was treated with high‑dose venlafaxine, which was continued throughout the entire clinical follow-up. This case highlights the challenges of managing severe, post‑stroke catatonia in the context of venous thromboembolism, intracerebral hematoma as well as the benefits of a multidisciplinary approach.